The effect of innovative instructions on pre-service science teachers’ conception about the nature of science: a scientific investigation / Beh Kian Lim - Beh, Kian Lim (Universiti Teknologi MARA, 2014)
Learning science without having a correct conception of the nature of science is a flaw in science education that warrants concern, all the more if science teachers teaching science have misconceptions about the nature of science. This paper is based on an action research carried out during Nature of Science (NOS)(SCE500) course for 56 pre-service science teachers in a science education programme. The study focuses on the learning outcomes on aspects of NOS that have been reported as common misconceptions among science learners. It specifically looks into the results of three aspects that are related to scientific investigation, i.e. its role, its demands on imagination and its process. The results show that after attending innovative lessons for a semester, the misconceptions of the pre-service science teachers regarding three aspects of NOS: experiments in science confirm scientific ideas, scientists use their imagination at the early stage of investigation only, and hypothesis-experiment-conclusion is a scientific method used by all scientists have reduced significantly.The paper also highlights in brief the innovative and creative elements pertaining to a variety of approaches used in the set induction of every class session based on the consensus mode of the Nature of Science. The paper concludes with the feedback on the course by the pre-service teachers.